Managing multiple chronic conditions in Singapore – Exploring the perspectives and experiences of family caregivers of patients with diabetes and end stage renal disease on haemodialysis. Issue 10 (2nd October 2016) - Lee, Vanessa Y.W.; Seah, Wei Ying; Kang, Augustine W.C.; Khoo, Eric Y.H.; Mooppil, Nandakumar; Griva, Konstadina
Abstract : Objective: Diabetes mellitus (DM) is the commonest cause of end stage renal disease (ESRD). Despite increasing DM-ESRD prevalence and high dependency on care, there is a lack of literature on DM-ESRD caregivers. We sought to explore the perspectives and experiences of caregivers of patients with DM undergoing haemodialysis in Singapore. Design: This study employed an exploratory, qualitative design comprising in-depth interviews with caregivers of DM-ESRD patients. Methods: Semi-structured interviews were conducted with a sample of 20 family caregivers (54.2 ± 12.6 years; 75% female) of DM-ESRD patients. Data were analysed using Thematic Analysis. Results: Key caregiving challenges identified were managing diet, care recipients' emotions and mobility dependence. Patients' emotional reactions caused interpersonal conflicts and hindered treatment management. Difficulties in dietary management were linked to patients' erratic appetite, caregivers' lack/poor understanding of the dietary guidelines and caregivers' low perceived competence. Limited resources in terms of social support and finances were also noted. Physical and psychological well-being and employment were adversely affected by caregiving role. Conclusion: This study highlights distinctive aspects of the DM-ESRD caregiving experience, which impact on caregivers' health and challenge care. Disease management programmes should be expanded to support caregivers in dealing with multimorbidity.